Harvesting and blending options for lower alcohol wines: a sensory and chemical investigation. (27th June 2017) - Longo, Rocco; Blackman, John W; Antalick, Guillaume; Torley, Peter J; Rogiers, Suzy Y; Schmidtke, Leigh M
Abstract: BACKGROUND: Lower alcohol wines often have a poor reputation among consumers, in part due to their unsatisfactory flavours such as reduced overall aroma intensity or herbaceous characters. The aim of this study, performed on Verdelho and Petit Verdot, was to quantify the effectiveness of a monovarietal blend in which wines made from less ripe grapes were blended with an equivalent volume of a wine vinified from riper fruit to produce wines with a lower alcohol content and desirable ripe fruit flavours. RESULTS: Eleven and 13 attributes, for Verdelho and Petit Verdot, respectively, were selected during sensory descriptive analysis. Intensities of perceived 'acidity', 'sweetness' and 'alcohol' attributes were significantly different ( P ≤ 0.05) between the blend (8.8 ± 0.1% v/v) and mature Verdelho (10.3 ± 0.1% v/v) wines, while no significant differences were found between the Petit Verdot blend (11.0 ± 0.1% v/v) and mature (12.6 ± 0.2% v/v) treatments. Volatile composition of wines was assessed using HS‐SPME‐GC‐MS. Partial least square regression suggested relationships between sensory descriptors and chemical attributes in the wines, as well as the modifications of sensory and compositional profiles following blending. CONCLUSIONS: The blending practice described allowed the production of wines with lower alcohol content while retaining similar sensory profiles of the later harvested, riper fruit wines. © 2017 Society of Chemical Industry